An Interesting Case of Neurobrucellosis Mimicking Neuropsychiatric Lupus. (8th July 2018) - Bains, Ramandeep; Dahhan, Tamara; Belzowski, Annie; Heinze, Emil R.; Wong, Andrew L.; Clements, Philip J.
Abstract : This case describes a patient presenting with acute onset papilledema, subacute strokes resulting in upper extremity weakness and numbness, arthritis, maculopapular rash, depressed C4 and CH50, and a high titer anti-double-stranded DNA antibody. The patient was given the diagnosis of probable systemic lupus erythematosus, which was supported by the Systemic Lupus International Collaborating Clinics (SLICC) criteria. He was aggressively treated for neuropsychiatric lupus (NPSLE) with pulse dose steroids and a dose of intravenous cyclophosphamide. Blood cultures drawn on admission later grew out 2/4 bottles of Gram-variable bacteria, speciated as Brucella melitensis by PCR. Serum Brucella serologies were also positive. On further evaluation, the patient noted a history of eating unpasteurized cheese in Mexico. Given these additional findings, the patient's presentation was most consistent with a diagnosis of neurobrucellosis. Steroids were tapered off, no further doses of cyclophosphamide were given, and a prolonged course of intravenous and oral antibiotic therapy was administered, resulting in complete resolution of the patient's presenting symptoms.